Colquioc archeology, Purisima river valley, middle basin of the Fortaleza, Ancash - van Dalen Luna, Pieter D. (2020)
In this article we present the results of the archaeological investigations carried out in the Colquioc annex, district of the same name. Archaeological surveys have allowed to record archaeological sites hitherto unknown to archeology, from the Early Horizon periods, made up of pyramidal structures; small domestic units and burial areas of the Late Intermediate Period; and the old town of Colonial dating, corresponding to the town of reduction foundation of the first century of Hispanic domination. The Colquioc area acquired strategic importance in pre-Hispanic periods due to its location, next to the confluence of the Fortaleza and Purisima rivers, being a meeting point for various groups through the Tinkuy.